Óleos essenciais no controle da ferrugem asiática em folíolos destacados de soja - Nascimento, Lucas dos Santos (2022)
Medicinal and aromatic plants can control phytopathogens due to the presence of natural compounds with antimicrobial action. The objective was to evaluate the effect of essential oils and alternative products on the control of Asian soybean rust on detached soybean leaflets. Four soybean leaflets without symptoms of rust were placed with the abaxial side facing up in an acrylic box on two sheets of paper towels moistened with distilled water. The P. pachyrhizi spore suspension was applied to the leaflets using a hand sprayer. Essential oils and alternative products were separately diluted in distilled water with 0.1% Tween 20 (v/v) at concentrations of 1, 10, 50 and 100 parts per million and applied to the leaflets immediately after inoculation, using a hand sprayer. Assessments were performed by visualizing the symptoms and comparing them with the diagrammatic scale for disease severity levels proposed by Godoy et al. 2006. The essential oils of Varronia curassavica access VCUR-105 and Ocimum basilicum from cultivars Edwina and Nufar F1 reduced the severity of asian rust in detached leaflets of soybean.